2009
DOI: 10.1351/pac-rep-08-04-03
|View full text |Cite
|
Sign up to set email alerts
|

Terminology for reversible-deactivation radical polymerization previously called "controlled" radical or "living" radical polymerization (IUPAC Recommendations 2010)

Abstract: This document defines terms related to modern methods of radical polymerization, in which certain additives react reversibly with the radicals, thus enabling the reactions to take on much of the character of living polymerizations, even though some termination inevitably takes place. In recent technical literature, these reactions have often been loosely referred to as, inter alia, "controlled", "controlled/living", or "living" polymerizations. The use of these terms is discouraged. The use of "controlled" is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
394
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 517 publications
(401 citation statements)
references
References 3 publications
5
394
0
2
Order By: Relevance
“…An IUPAC task group has recently recommended the term reversible deactivation radical polymerization (RDRP) to describe polymerizations, such as ATRP, NMP, or RAFT, that entail equilibria between active and dormant chains. [4] This term is not intended to have any connotations as to the fraction of living chains that might be present in a particular polymerization process. It remains acceptable to use the term 'living radical polymerization'to describe a hypothetical process in which termination is indeed absent.…”
Section: San H Thang Completed His Bsc (Hons) In 1983 and Phd Inmentioning
confidence: 99%
See 1 more Smart Citation
“…An IUPAC task group has recently recommended the term reversible deactivation radical polymerization (RDRP) to describe polymerizations, such as ATRP, NMP, or RAFT, that entail equilibria between active and dormant chains. [4] This term is not intended to have any connotations as to the fraction of living chains that might be present in a particular polymerization process. It remains acceptable to use the term 'living radical polymerization'to describe a hypothetical process in which termination is indeed absent.…”
Section: San H Thang Completed His Bsc (Hons) In 1983 and Phd Inmentioning
confidence: 99%
“…[117,130,479] This methodology has been applied to the synthesis of three-armed stars by an in-situ thiol-ene reaction with a triacrylate [130] and has been applied to directly make biopolymer conjugates. [479] A recent study shows that dithioester and trithiocarbonate RAFT agents [R-SC(S)Z] undergo a radical-catalyzed reaction with thiols that results in oxidation of the thiol to a disulfide and concomitant reduction of the RAFT agent to R-H. [481] The relative rates of reaction suggested that dithioester RAFT agents [204] PEGA Ph (58) Butylamine Used in thiol-ene [204] NIPAM SCH 2 CH(CH 3 ) 2 (188) Butylamine/TCEP/HEA butylamine/TCEP/BA One-pot thiol-ene [373] NIPAM SCH 2 CH(CH 3 ) 2 (188) Butylamine/TCEP Used in thiol-ene [371,372] NIPAM Ph (25) LiB(C 2 H 5 ) 3 H Used in thiol-ene [151] NIPAM S(CH 2 ) 2 CO 2 H (170) NaBH 4 Used in thiol-ene [355] NIPAM SC 4 H 9 (166) NaOH/MeOH/EDTA Used in thiol-ene [412] NIPAM Ph (24) Octylamine/DMPP/AMA One-pot thiol-ene [132] NIPAM Ph (24) Octylamine/DMPP/PMA One-pot thiol-ene [132] DEAM Ph (24) Hexylamine/DMPP/MA One-pot thiol-ene [130] St Ph (24) Propylamine/PBu 3 /MA NaBH 4 /PBu 3 /MA One-pot thiol-ene [117] St Ph (24) Propylamine NaBH 4 [205] MMA Ph (82) Hexylamine Conditions to favour disulfide formation [196] MMA Ph (22) Propylamine One-pot methanethiosulfonate [480] NVP OC 2 H 5 (228) NaBH 4 Used in peptide/nucleotide conjugation [396] A Monomer unit adjacent to thiocarbonylthio group. B TCEP -tris(2-carboxyethyl) phosphine hydrochloride, EDTA -ethylenediaminetetraacetic acid, TCEP -tris(2-carboxyethyl phosphine), DMPPdimethylphenylphosphine.…”
Section: Aminolysis/hydrolysis/ionic Reductionmentioning
confidence: 99%
“…31 Additionally, if amphiphilicity of the resulting polymers is aspired, the synthesis of star block copolymers or controlled hydrophobic end-capping of the star polymers becomes a necessity. Both structural features are achieved using either (mostly ionic) living polymerisation techniques or the techniques of reversible-deactivation radical polymerisation (RDRP), 32 often referred to as controlled radical polymerisation (CRP). Living ionic polymerisations, however, are in general infamous for their sensitivity to air, water and most functional moieties.…”
Section: -24mentioning
confidence: 99%
“…An IUPAC task group has recommended the use of a new term (controlled) reversible deactivation radical polymerization (RDRP) to describe polymerizations, such as ATRP, NMP or RAFT, which entail equilibria between active and dormant propagating species. [14] This term is not intended to have any connotations as to the fraction of living chains that might be present in a particular polymerization process and does not imply any particular degree of control.…”
Section: Introductionmentioning
confidence: 99%